Psychological Antecedents of Refugee Integration (PARI). (July 2020) - Echterhoff, Gerald; Hellmann, Jens H.; Back, Mitja D.; Kärtner, Joscha; Morina, Nexhmedin; Hertel, Guido
The successful management of refugee immigration, including refugee integration in host societies, requires a sound understanding of underlying psychological processes. We propose the psychological antecedents of refugee integration (PARI) model, highlighting perceived forcedness (i.e., coercion and loss of control from "push" factors) and ensuing perils (risks and potential suffering during migration) as distinctive factors of refugee (vs. voluntary) migration. According to our model, perceptions and subjective representations of forcedness and associated perils activate specific psychological processes relevant to refugee integration and thus moderate responses to the demands and stressors of the immigration situation. We conceptualize these distinctive influences for integration-relevant processes in both refugees and in residents. By pinpointing the unique features of refugee migration, PARI generates novel and specific hypotheses about psychological processes predicting refugee integration. For instance, refugees' memories of forcedness and associated perils should lead to a high level of preoccupation with the restoration of basic needs after arrival in a receiving country that interferes with integration-related activities. Conversely, residents' perceptions of forcedness and related perils may enhance empathy with refugees but may also magnify feelings of anxiety and threat. Implications for refugee integration are discussed for the domains of occupational work, education, and mental health.